FUT-LAMA: RECREATION OR SPORTS? (Fiep Bulletin - online, 2013)
The banks of the Amazon River, the largest in the world, in the city Macapá, capital of the state of Amapá, northern Brazil, due to a customary recreation on the weekends, was born the fut-lama. The name fut-lama occurs because it is a soccer game held in a field that, instead of grass, is completely taken by mud. Lately, this activity has gained notoriety in national and international scenario, because it unique in the region. Since the year 2002, the Prefecture Macapá has organized a state championship, aiming to enhance and disseminate the "sport" that each day gains more supporters. Sport in quotes, because there is the question the real reasons of fut-lama as such. With adequate investment and projects, the acceptance of the fut-lama mode as sports will be inevitable, especially if there is the possibility of professionalism and greater disclosure of activity in the academic environment. The objective of this work is to make the population, authorities and institutions of the State of Amapá to watch in fut-lama the opportunity to build a sports own identity and will use fut-lama as a means of inclusion and socio-educational promote tourism in the region.